2009
DOI: 10.1111/j.1420-9101.2009.01751.x
|View full text |Cite
|
Sign up to set email alerts
|

Hidden support from unpromising data sets strongly unites snakes with anguimorph ‘lizards’

Abstract: A combined analysis of nuclear, mitochondrial and morphological data robustly resolves snakes as the sister taxon to anguimorph ‘lizards’. Analysed in isolation, nuclear DNA (nDNA) produces a trichotomy between snakes, iguanians and anguimorphs, mitochondrial DNA (mtDNA) is largely uninformative at deeper levels, and morphology tends to nest snakes deep within anguimorphs or with various legless squamate groups. When analysed simultaneously, the nuclear signal is sufficiently strong that mtDNA and morphology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 35 publications
5
40
0
2
Order By: Relevance
“…We further corroborate previous studies in also placing Anguimorpha with Iguania [16-20]. In contrast, some other studies have placed anguimorphs with snakes as the sister group to iguanians [127,128]. …”
Section: Resultssupporting
confidence: 91%
“…We further corroborate previous studies in also placing Anguimorpha with Iguania [16-20]. In contrast, some other studies have placed anguimorphs with snakes as the sister group to iguanians [127,128]. …”
Section: Resultssupporting
confidence: 91%
“…However, examination of phylogenies resulting from individual genes revealed that topological incongruence was generally limited to certain poorly supported nodes. It has been suggested that different data sets may have a common phylogenetic signal recoverable only upon combined analysis [47,48], and, under the hypothesis that combining data from multiple genes may potentially overcome misleading signal in individual genes [49], we conducted further analyses to compare results from a concatenated data set with results obtained from ML and BI.…”
Section: Resultsmentioning
confidence: 99%
“…Statistical tests were performed using a consensus phylogeny derived from several published phylogenies (Motokawa, 2004;Livezey & Zusi, 2007;Lee, 2009Lee, , 2013Kan et al, 2010;Meredith et al, 2011;Yu et al, 2011;Hedges, 2012;Wiens et al, 2012;Yang et al, 2013; Fig. Statistical tests were performed using a consensus phylogeny derived from several published phylogenies (Motokawa, 2004;Livezey & Zusi, 2007;Lee, 2009Lee, , 2013Kan et al, 2010;Meredith et al, 2011;Yu et al, 2011;Hedges, 2012;Wiens et al, 2012;Yang et al, 2013; Fig.…”
Section: Figurementioning
confidence: 99%